Multidisciplinary: The cerebrovascular response to ketamine: a systematic review of the animal and human literature. (3rd June 2015) - Zeiler, FA; Sader, N; Gillman, LM; Teitelbaum, J; West, M; Kazina, CJ
Abstract : Introduction: Ketamine, an N-methyl D-aspartate (NMDA) receptor antagonist, carries potential benefit in patients with neurological illness. The cerebrovascular/cerebral blood flow (CBF) response to ketamine has been poorly outlined in the literature. Methods: We performed a systematic review of the literature on the cerebrovascular/CBF effects of ketamine in both animal and human subjects. Results: We identified 38 animal studies, and 20 human studies. Within the animal studies, a variety of different models were utilized with the majority focusing changes in global CBF or regional cerebral blood flow (rCBF). Overall, ketamine led to an increase in either global CBF or rCBF, with a vasodilatory effect in medium cerebral vessels. With the human studies a total of 379 patients, 107 of which were control subjects, were studied. Most studies focused on either 131Xe CT or PET imaging with ketamine administration. There was a trend to an increase in global CBF and rCBF with ketamine administration. Conclusions: Animal models indicate an increase in global CBF and rCBF with ketamine administration. Human studies display an Oxford 2b, GRADE C, level of evidence to support an increase in global CBF and rCBF with ketamine administration in both healthy volunteers and elective surgical patients without neurological illness.